Post-depositional processes studies of wooden artifacts from the 18th century Swift shipwreck site (Patagonia, Argentina) - Grosso, Mónica (2014)
The HMS Swift was a British Navy sloop-of-war that sank off the Patagonia coast in 1770. The Swift shipwreck site, on the northern coast of Santa Cruz Province (Argentina), is a well-preserved underwater archaeological site. The high frequency of wooden artifacts at the site permitted the development of specific research designed to identify the primary natural and cultural post-depositional processes related to the preservation and spatial distribution of those artifacts. This paper presents the methodological framework for this research, which included both direct observations and experimental studies that led to the characterization of the organisms related to the shipwreck site and their interaction with archaeological materials. Results confirm that sedimentary conditions have played a central role in the preservation of wooden materials and their spatial distributions. Furthermore, the archaeological consequences of organisms’ damaging activities (mainly those of marine wood-borer mollusks) are assessed.